LUXURY TOURISM CONSUMERS’ MODEL. ISSUES RELATING TO CONSUMER SATISFACTION AND BEHAVIOURAL INTENTION (Revista Inclusiones, 2021)
Satisfaction is a problem that is constantly provoking the attention of theory and practice in tourismindustry. And if for the mass forms of tourism satisfaction is partially dependent on price, thenregarding the luxury tourism its performance is the result of the proceeding of specific and oftenirrational effects. Building on such an unconventional starting point, the present study aims to deploytheoretically and to propose an explanation of luxury tourism behaviour by exploring well-establishedconsumer models. The purpose is to trace the boundary markers of satisfaction for "luxury" touristsin order to identify the possibilities for their inclusion in a particular model. Luxury is a sign of socialstratification, in which the understanding of the driving mechanisms determines the ability to establishits underlying principles. By analysing and understanding the essence and mechanisms of luxury, itis seeming that the idea and aspirations for lux are deeply rooted in human nature. The research isdetermined by the perception that luxury is an integral part of humanity and way of life in humansocieties and explores the link between behavioural intention and consumer satisfaction.